Tax Compliance and Economic Growth of Nigeria: The Moderating Effect of Tax Morale - Odukwu Chika Victory; Eke Promise; Effiong Udo Etok; Karimo Perry Erepamo (Journal of Corporate Finance Management and Banking System ( JCFMBS) ISSN : 2799-1059, 2023)
Getting the citizens to comply with tax payment is a herculean task for policy makers in developing economics like Nigeria. Therefore, the researchers investigated tax compliance and economic growth: Moderating effect of tax morale. The quantitative research design adopted was found to be appropriate for the quantitative research model that underpins the study at hand. Also, descriptive statistics was used to explain the study’s variables. The secondary data were sourced from the Statistical Bulletin of CBN and the National Bureau of Statistics (2022). A regression analysis was adopted to analyze the data so collected. Moreover, the panel regression is a veritable for re-occurring observation of the same variable for several times or periods. While the control variables are the Gross Domestic Product (GDP) and the Human Development Index (HDI), the components of tax compliance are proxied as logged revenue and as the independent variable. Moreover, tests for robustness were run, including simple regression, to validate the result's dependability while also taking into account all of the assumptions related to regression. Findings revealed that there is a negative significant effect of tax compliance (TAXCOMPL) on economic growth (HDI) of Nigeria, there is a positive significant impact of tax compliance (TAXCOMPL) on economic growth (RGDP) of Nigeria, also, there is a significant weak moderating effect of tax morale on tax compliance and Nigeria's economic growth. In the light of the above, the researcher made the following suggestions; government should provide essential services to the people to enhance voluntary tax compliance. To motivate tax payers, policy makers should translate taxes collected into human capital development to boost economic growth.